2021
DOI: 10.1186/s12871-021-01441-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dexmedetomidine supplemented analgesia on delirium in patients recovering from orthopedic surgery: A randomized controlled trial

Abstract: Background Dexmedetomidine promotes normal sleep architecture; the drug also improves analgesia. We therefore tested the hypothesis that supplementing intravenous analgesia with dexmedetomidine reduces delirium in older patients recovering from orthopedic surgery. Methods In this double-blinded randomized controlled trial, we enrolled 712 older (aged 65–90 years) patients scheduled for major orthopedic surgery. Postoperative analgesia was provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…This randomized clinical trial investigated the effect of 0, 200, and 400 μg of DEX combined with sufentanil for PCA on postoperative sleep quality and the recovery of gastrointestinal motility function in patients after colorectal cancer surgery. Our results demonstrated that the continuous infusion of 200 and 400 μg of DEX for PCA after surgery improves sleep quality in the Studies have shown that DEX used for PCA at a rate of 0.03 μg/kg/h improves postoperative sleep quality (Chen et al, 2017;Hong et al, 2021). The total dosage of DEX used in this study was 0.03-0.05 and 0.07-0.09 μg/kg/h according to the body weight of enrolled patients in the DEX 200 μg group and DEX 400 μg group, respectively, which was higher than that used in the above report.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This randomized clinical trial investigated the effect of 0, 200, and 400 μg of DEX combined with sufentanil for PCA on postoperative sleep quality and the recovery of gastrointestinal motility function in patients after colorectal cancer surgery. Our results demonstrated that the continuous infusion of 200 and 400 μg of DEX for PCA after surgery improves sleep quality in the Studies have shown that DEX used for PCA at a rate of 0.03 μg/kg/h improves postoperative sleep quality (Chen et al, 2017;Hong et al, 2021). The total dosage of DEX used in this study was 0.03-0.05 and 0.07-0.09 μg/kg/h according to the body weight of enrolled patients in the DEX 200 μg group and DEX 400 μg group, respectively, which was higher than that used in the above report.…”
Section: Discussionmentioning
confidence: 55%
“…Studies have shown that DEX used for PCA at a rate of 0.03 μg/kg/h improves postoperative sleep quality ( Chen et al, 2017 ; Hong et al, 2021 ). The total dosage of DEX used in this study was 0.03–0.05 and 0.07–0.09 μg/kg/h according to the body weight of enrolled patients in the DEX 200 μg group and DEX 400 μg group, respectively, which was higher than that used in the above report.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, low-dose dexmedetomidine infusion at night improved sleep quality without increasing adverse events in postoperative ICU patients, the majority of whom did not receive invasive mechanical ventilation ( 22 , 23 ). Subsequent studies showed that low-dose dexmedetomidine combined with opioids also improves analgesia and subjective sleep quality ( 43 , 44 ). Chen et al ( 45 ) reported that dexmedetomidine administered at a rate of 0.05–0.08 μg/kg/h via a patient-controlled analgesia pump improved the sleep structure ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…205 Dexmedetomidine supplemented analgesia may also reduce delirium but requires further investigation. 206…”
Section: Sleep Promotionmentioning
confidence: 99%
“…It is worthy to note that an even lower dose of dexmedetomidine, such as used as an adjuvant in the patient‐controlled analgesia pump, also improves sleep quality after surgery 205 . Dexmedetomidine supplemented analgesia may also reduce delirium but requires further investigation 206 …”
Section: Prevention For Perioperative Ncdsmentioning
confidence: 99%